Profiling of Circadian Genes Expressed in the Uterus Endometrial Stromal Cells of Pregnant Rats as Revealed by DNA Microarray Coupled with RNA Interference - Tasaki, Hirotaka; Zhao, Lijia; Isayama, Keishiro; Chen, Huatao; Yamauchi, Nobuhiko; Shigeyoshi, Yasufumi; Hashimoto, Seiichi; Hattori, Masa-Aki (Frontiers in Endocrinology, 2013)
The peripheral circadian oscillator plays an essential role in synchronizing local physiology to operate in a circadian manner via regulation of the expression of clock-controlled genes. The present study aimed to evaluate the circadian rhythms of clock genes and clock-controlled genes expressed in the rat uterus endometrial stromal cells (UESCs) during the stage of implantation by a DNA microarray. Of 12,252 genes showing significantly expression, 7,235 genes displayed significant alterations. As revealed by the biological pathway analysis using the database for annotation, visualization, and integrated discovery online annotation software, genes were involved in cell cycle, glutathione metabolism, MAPK signaling pathway, fatty acid metabolism, ubiquitin mediated proteolysis, focal adhesion, and PPAR signaling pathway. The clustering of clock genes were mainly divided into four groups: the first group was Rorα, Timeless, Npas2, Bmal1, Id2, and Cry2; the second group Per1, Per2, Per3, Dec1, Tef, and Dbp; the third group Bmal2, Cry1, E4bp4, Rorβ, and Clock; the fourth group Rev-erbα. Eleven implantation-related genes and 24 placenta formation-related genes displayed significant alterations, suggesting that these genes involved in implantation and placenta formation are controlled under circadian clock. Some candidates as clock-controlled genes were evaluated by using RNA interference to Bmal1 mRNA. Down-regulation of Igf1 gene expression was observed by Bmal1 silencing, whereas the expression of Inhβa was significantly increased. During active oscillation of circadian clock, the apoptosis-related genes Fas and Caspase3 remained no significant changes, but they were significantly increased by knockdown of Bmal1 mRNA. These results indicate that clock-controlled genes are up- or down-regulated in rat UESCs during the stage of decidualization. DNA microarray analysis coupled with RNA interference will be helpful to understand the physiological roles of some oscillating genes in blastocyst implantation and placenta formation.